Norepinephrine infusion improves haemodynamics in the preterm infants during septic shock. (26th October 2017) - Rizk, MY; Lapointe, A; Lefebvre, F; Barrington, KJ
Abstract: Aim: This study evaluated the clinical and haemodynamic effects of norepinephrine infusion in preterm infants. Methods: The effects of norepinephrine therapy for refractory hypotension were evaluated in preterm infants between April 2009 and April 2011 at the neonatal intensive care unit of Sainte‐Justine Hospital, Montreal, Quebec. Changes in haemodynamics and clinical parameters were analysed eight hours before and eight hours after the start of norepinephrine infusion, and eight hours after its cessation. Results: During the study, 30 preterm infants at a mean gestational age of 26.5 ± 2.6 weeks (median: 25.7, 23.4–34) and birthweight of 903 ± 437 g (median 827, 450–2550) received norepinephrine infusion for neonatal septic shock. After eight hours of treatment, mean blood pressure, urine output and FiO2 significantly improved. Eight hours after cessation of norepinephrine infusion, the number of patients treated with other inotropes decreased significantly, 24 patients (80%) had normal mean blood pressure and 27 patients (90%) had normal urine output. Conclusion: Norepinephrine therapy could be considered to improve blood pressure and urine output during neonatal septic shock in preterm infants. Further studies are needed to prove the efficacy and safety of norepinephrine infusion in neonates.